Microorganisms of soil ecosystems and their health - Mihailovič-Semenov Aleksander; Đukić Dragutin; Leka Mandić (Acta Agriculturae Serbica, 2019)
The current (at the end of the first quarter of the 21 century) ideas about the microbial community (MC), structure and concepts reflecting and summarizing progress in the knowledge of the MC are considered. The ideas about the microbial community are discussed from the point of view of modern knowledge of the role and functions of microbial communities in the emergence and maintenance of a product that is traditionally called a rather short and succinct term-soil, but which, in essence, is a product of interactions of various biological communities and substances which is infinitely multi-valued and differently conceptual, and is an ecosystem, a soil ecosystem (SE). It justifies the need to develop a new concept for the knowledge of this product-soil health (SH), as an integration of modern knowledge of MCs and their functions. Methods for determining the parameters of soil health are briefly described.